1997
DOI: 10.1093/geront/37.3.324
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Geriatric Evaluation and Management: Is There an Investment Effect?

Abstract: The effectiveness and efficiency of outpatient geriatric evaluation and management (GEM) was compared to usual outpatient primary care (UPC). Although GEM had no overall impact on health care utilization or cost of care for the entire study period, significant reductions were found during the sixteen- to twenty-four-month study period, suggesting a possible investment effect. In the first eight months of the study, GEM patients incurred 34.8% more in health care costs than UPC patients, but in the final eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
1
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 0 publications
0
52
1
1
Order By: Relevance
“…This idea is consistent with the GEM clinic investment effect found by Toseland et al, in a study with a 24-month follow-up period. 27 There are several limitations to our study. By design, this study was limited to patients, mostly men, within the VA Health Care System.…”
Section: Discussionmentioning
confidence: 94%
“…This idea is consistent with the GEM clinic investment effect found by Toseland et al, in a study with a 24-month follow-up period. 27 There are several limitations to our study. By design, this study was limited to patients, mostly men, within the VA Health Care System.…”
Section: Discussionmentioning
confidence: 94%
“…[5][6][7]16 Specifically, 5 cluster-randomized trials have examined the effect of functional patient-centered medical home interventions on these outcomes. [17][18][19][20][21] Two of the 3 trials reporting data on outpatient ED use showed a reduction; both of those populations included older adults similar to the Medicare population. 15,16 When data from these 2 studies were combined, the relative risk reduction in ED use was 0.81 (95% CI 0.67 to 0.98), similar to the magnitude of our observed reductions.…”
Section: Discussionmentioning
confidence: 99%
“…32,33,38 Not surprisingly, only a handful of studies are able to demonstrate a survival benefit from outpatient GEM interventions. 31,33,39,41 In general, costs associated with outpatient GEM services do not differ significantly from usual outpatient care, 30,33,34,37,42 and may decline with continued implementation of the service, suggesting a possible investment effect. 42 In summary, although of smaller magnitude than for inpatient GEM interventions, substantial evidence exists for the effectiveness of outpatient GEM interventions in maintaining and/or improving function of community patients, irrespective of the intervention environment.…”
Section: Outpatient Gem Interventionsmentioning
confidence: 97%